2015
DOI: 10.1186/1479-5868-12-s1-s3
|View full text |Cite
|
Sign up to set email alerts
|

Educational outcomes associated with childhood obesity in the United States: cross-sectional results from the 2011–2012 National Survey of Children’s Health

Abstract: BackgroundPast research examining the effects of childhood obesity has largely focused on its projected effects into adulthood. However, there is emerging evidence that childhood obesity may have more immediate effects on school-related outcomes. We examine a range of educational attainment indicators to examine the possible pathway between obesity status and academic performance, while investigating the proximal effects of childhood obesity on health and utilization of health services, and whether these varia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
48
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(52 citation statements)
references
References 45 publications
1
48
1
2
Order By: Relevance
“…These results are not in agreement with other studies and systematic reviews which reported a negative and significant association between overnutrition of children or teenagers and SA [29,30,31,32,33,34,35]. It is unclear why overnutrition did not show a significant correlation with SIMCE 2009 outcomes in our study where most part of the sample presented with overnutrition (56.7% and 51.8% of men and women, respectively).…”
Section: Discussioncontrasting
confidence: 57%
“…These results are not in agreement with other studies and systematic reviews which reported a negative and significant association between overnutrition of children or teenagers and SA [29,30,31,32,33,34,35]. It is unclear why overnutrition did not show a significant correlation with SIMCE 2009 outcomes in our study where most part of the sample presented with overnutrition (56.7% and 51.8% of men and women, respectively).…”
Section: Discussioncontrasting
confidence: 57%
“…Thus, obesity and obesity‐related comorbidities are a significant concern for Hispanics. Because of the significant health and social consequences associated with obesity, identifying time periods when children are at increased risk for gaining weight is essential. Identifying critical time periods may facilitate the development of more targeted programs to address the obesogenic behaviors specifically, when they are more likely to occur.…”
mentioning
confidence: 99%
“…Children in receipt of natural or informal mentoring were defined as children whose parents/guardians responded positively to the survey question on whether there is at least one other adult in child's school, neighborhood, or community, other than the child's parents or adults in the child's home, who knows the child well and who the child can rely on for advice or guidance. Our definitions and operationalization of study variables were consistent with prior studies and the literature on natural mentoring, bullying, and educational outcomes …”
Section: Methodsmentioning
confidence: 66%
“…Logistic regression was used to examine the bivariate and adjusted associations between mentoring and the 3 outcome variables. Using the social‐determinants‐of‐health (SDH) framework, drawing upon the social cognitive theory (SCT), and past research as guides, we developed a conceptual framework for explaining the relationship between our study variables underscoring the proximate and distal roles of sociodemographic and natural mentoring relationships in influencing bullying and educational outcomes (Figure ) . The SDH refer to the conditions in which people are born, grow, live, work, and age, all of which are shaped by the distribution and availability of human and material resources to individuals living at the local to the global levels .…”
Section: Methodsmentioning
confidence: 99%